DAMPAK REKRUTMEN DAN PELATIHAN KERJA TERHADAP KINERJA KARYAWAN: Studi Kasus PT Kinarya Anak Negeri (Klenger Burger) - Fitriyadi, Enjah Pipit; Kustini, Endang; Putri, Aldila Rahma; Darmadi, Darmadi; Pratama, Guruh Dwi (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2024)
The aim of this study is to assess the combined impact of employee recruitment and training on the performance of PT Narya Anak Negeri (Klenger Burger) employees. Employing a quantitative approach, the study utilized saturated sampling, involving 75 respondents who are employees of PT Narya Anak Negeri (Klenger Burger). Statistical analyses encompassed validity and reliability testing, classical assumption testing, simple linear analysis, multiple linear regression, determination coefficient computation, as well as hypothesis testing using t-tests and F-tests. Findings indicate that Recruitment (X1) significantly enhances Employee Performance (Y), as evidenced by a calculated t value (8.604) surpassing the critical t value (1.666). Similarly, Job Training (X2) demonstrates a positive and significant impact on Employee Performance (Y), with a calculated t value (7.553) exceeding the critical t value (1.666). Moreover, simultaneous Recruitment (X1) and Job Training (X2) jointly exert a positive and significant influence on Employee Performance (Y), as indicated by an F value (44.156) surpassing the critical F value (2.73), with a probability significance of 0.000 < 0.05. Consequently, the null hypothesis (H0) is rejected in favor of the alternate hypothesis (H3), affirming a simultaneous positive and significant relationship between Recruitment and Job Training on Employee Performance at PT Narya Anak Negeri (Klenger Burger).